Forced Exile and International Career: an Isolated Paradox? The Case of Abbé Raynal and the Histoire des deux Indes - Sempère, Emmanuelle (Sensus Historiae, 2024)
This paper looks at the paradoxical effect of oppression on critical thought through the case of Raynal and Diderot, respectively the author and anonymous contributor to the Histoire des deux Indes (1770–1781). The former’s happy exile and the latter’s threatened security jointly forged this polemical summation of Enlightenment ideas on colonisation.